Differences in blood pressure before and after consuming cucumber juice (Cucumis sativus) in women aged 30-40 years - Franklin, Martin; Haroen, Edeh Roletta; Tjahajawati, Sri (Universitas Padjadjaran, 2010)
Introduction: Cucumber contains pottasium that can decrease blood pressure. This study was implemented to obtain data about the difference in blood pressure before and after consuming cucumber essence (Cucumis sativus) at women aged 30-40 years. Aim of this research is to analyzed difference s of blood pressure between before and after consuming cucumber essence (Cucumis sativus) at women aged 30-40 years. Methods: This study was a quasi-experimental with pair measurement statistic data test. Total samples of this study were 30 women at RW 02, Sukawarna district, Sukajadi, house of the village-head. Results: the average of systole before consume cucumber essence was 119,29 mmHg and after to be 115,09 mmHg. The average of diastole before consume cucumber essence was 80,91 mmHg and after to be 78,16 mmHg. Statsitic analysis showed if α = 0,05 (t0,975) value of tcalc both systolic and diastolic blood pressure > ttable so that H0 rejected and H1 accepted. Conclusion: this study showed a difference in blood pressure between before and after consuming cucumber essence (Cucumis sativus) at women aged 30-40 years.